Maternal Mortality - Maradiegue Méndez, Eduardo (2015)
Safeguarding health is implicit in the work of the medical and social sciences and motherhood remains the most important and momentous in the life of women process is necessary to provide high quality care with the aim of achieving safe motherhood, without risk for the mother and the conceptus. Maternal mortality is a crucial public health problem in Peru that need solving, not just for the medical conditions that cause, but by the socio-economic and cultural problems that arise and their consequences that lead to profound imbalances family and social.